PENERAPAN MODEL KOOPERATIF TIPE STAD DISERTAI KAHOOT GAME DALAM PEMBELAJARAN MATEMATIKA PESERTA DIDIK KELAS XI SMAN 1 SIBERUT SELATAN - Rosalinda, Rosalinda; Rahmi, Rahmi; Anggraini, Villia (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research was motivated by the low mathematics learning outcomes of students. The aim of this research is to find out whether the mathematics learning outcomes of students using the STAD type cooperative model accompanied by the Kahoot game are better than the learning outcomes of students using the conventional learning model in class XI MIA SMAN 1 Siberian Selatan. The type of research used is experimental research with a Control-Group Post-Only design. The population in this study were students of class The sampling technique was carried out randomly. The classes selected were class XI MIA 1 as the experimental class and class XI MIA 2 as the control class. The research instrument was a final learning test in the form of an essay. The data analysis technique used is the one-sided t test, namely the right side. Based on data analysis, the hypothesis results obtained=1.714 and=1.669 with a level of ? = 0.05, thenso it can be concluded that the results of students' mathematics learning by applying the cooperative model The STAD type accompanied by the Kahoot game is better than the mathematics learning outcomes of students who apply conventional learning.